Fontes e doses de silicato no rendimento agrícola e na qualidade tecnológica da cana-de-açucar - Leite, Gustavo Melasipo Vilela (2006)
One experiment was established on a Yellow-red Latosol Distrophic soil, located at "João Mendes" - JM sugarcane distillery, Perdões, county, MG, Brazil to evaluate sources and doses of silicate on sugarcane, SP 80-1816 var., production. The experimental design was a randomized block in a 3 x 3 + 1 factorial scheme with three calcium silicate sources ("Silifertil", "Extrativa", and "Agronelli") at three doses (150, 300, and 450 kg.ha-1) plus one additional treatment without silicate, making 10 treatments. Silicate sources and doses were applied at planting furrow together with NPK fertilizer. Calcium silicate applied at planting furrow promoted increase in sugarcane fiber percentage and decrease in number of harvested stalk although did not affect stalk yield and recovered total sugar (RTS) regardless the source or dose applied.